Improving palliative and end-of-life care for rural and remote Australians - Sarah Wenham; Melissa Cumming; Emily Saurman (Sax Institute, 2020)
Recent reports highlight an inconsistent provision of palliative and end-of-life (palliative) care across Australia, particularly in regional, rural and remote areas. Palliative care improves quality of life and the experience of dying, and all people should have equitable access to quality needs-based care as they approach and reach the end of their lives. A palliative approach to care is crucial in rural and remote Australia where there is a reliance for such care on generalist providers amid the challenges of a limited workforce, poorer access, and vast geography. This article describes the development and implementation of the Far West NSW Palliative and End-of-Life Model of Care, a systematic solution that could drive improvement in the provision of a quality palliative approach to care and support from any clinician in a timely manner, for patients, their families and carers anywhere.